Superior reproducibility and femoral tunnel angulation with hybrid transtibial vs. anteromedial portal techniques in ACL reconstruction: a retrospective case-control study - Li, Jiatong; Wang, Jie; Yang, Qingjun; Huang, Xiancheng; Luo, Yong; Ye, Sufen; Lun, Haochi; You, Tian (Frontiers in Surgery, 2025)
IntroductionThere are two traditional methods of femoral tunnel drilling during anterior cruciate ligament reconstruction (ACLR), transtibial (TT) or anteromedial portal (AM). However, both these approaches have specific disadvantages. Recently, a new technique combining the advantages of both approaches while avoiding their drawbacks has been developed, hybrid transtibial (HTT). The aim of the present study was to compare the radiology of the HTT and AM techniques in patients undergoing ACLR.MethodsWe retrospectively analysed the three-dimensional computed tomography data of 31 patients who underwent ACLR (HTT and AM) at our institution between 29 October 2019 and 6 February 2023. The distance between the actual bone tunnel position and the standard anatomical location was measured in both the anterior–posterior and superior–inferior directions and expressed as a percentage. The spatial graft bending angle between the tibial and femoral tunnels was evaluated using Mimics software.ResultsThirty-one patients were included in the study: 12 and 19 in the AM and HTT groups, respectively. Compared with the AM group (9.71 ± 3.96, 9.37 ± 3.41), the HTT group had significantly smaller percentage distances t% (4.54 ± 2.76) in the anterior and posterior directions, and percentage h% (6.84 ± 2.66) in the upward and downward directions (P = 0.0002, P = 0.0281). The bending angles of the grafts in the AM and HTT groups were 103.79 ± 8.49 and 115.22 ± 9.72, respectively (P = 0.002), and the AM composition angle was more pronounced.ConclusionsThe HTT technique exhibits superior repeatability in femoral tunnel drilling compared to the AM technique, facilitating more consistent achievement of the optimal graft bone tunnel position. Moreover, the graft bending angle observed with the AM technique is more pronounced than with HTT, which likely increases the forces exerted on the graft at the shallow edge of the tunnel aperture.